Anticorrosive bitumen compositions with petroleum resins; IFOST 2012; Vol. 1 - Slavgorodskaya O. I. Olga Igorevna (Section 1. Chemical engineering and "Green technology", 2012)
The process of petroleum resin epoxidation obtained by thermal polymerization of C9 fraction of liquid pyrolysis products has been investigated. The influence of various factors on the modification process has been established. The possibility of using a modified petroleum resin as a component polymeric-bitumen compositions with high anticorrosive and physical-mechanical characteristics has been shown.